ISLAMIC MORAL IDEAS AND POLITICS: ULAMA ACTIVIST HADRATUS SHEIKH HASYIM ASY'ARI AND SHEIKH NAWAWI AL BANTANI - Baydi, Ubaidillah; Hibbi Farihin; Ali Abdurrahman (UIN Raden Mas Said Surakarta, 2024)
The article aims to provide an overview of the fundamental ideas in Indonesian national political settings, as well as their significance in solidifying the four pillars of Indonesian identity. Based on a library study of the works of two great Indonesian Ulama, Sheikh Nawawi al-Bantani and Sheikh Hasyim Asy'ari, which were later analyzed using the content analysis method, the results revealed that the theological principles of the masters' actions in both the Qur'an and the hadith remained the basis of obedience, unity, brotherhood, and solidarity. Sheikh Nawawi al-Bantani generally supports components of national commitment, conservation, and natural resource management in the political Islamic framework, and he does not oppose the concept of truth. While Sheikh Hasyim Asy'ari emphasized characteristics of government management such as leadership maturity, unity, and brotherhood, which resulted in the formation of the four national pillars as a consensus among the nation's citizens.